1988
DOI: 10.1210/endo-122-2-389
|View full text |Cite
|
Sign up to set email alerts
|

1,25-Dihydroxycholecalciferol-Dependent Calcium Uptake by Mouse Mammary Gland in Culture*

Abstract: Mammary explants from pregnant mice cultured in the presence of lactogenic hormones express their differentiated function by producing milk components in vitro. In the present paper radioactive calcium uptake was studied in the mammary gland during terminal differentiation, when lactogenesis was initiated. Under these conditions a relevant accumulation of calcium in the tissue was clearly demonstrable. We have characterized the calcium uptake by the tissue as a saturable and energy dependent process. When 1,25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…In our present study, we found that the preconfluent cells grown in 0.03 mM Ca had an acute Cai response to 2 mM Cao, and this response is further enhanced when cells were treated for 24 h with 1,25(OH) 2 D 3 . A similar effect of 1,25(OH) 2 D 3 on Cai has been observed in other cell systems (Hruska et al, 1988;Bikle, 1990;Pillai et al, 1995;Mozzetti et al, 1988). In these systems, 1,25(OH) 2 D 3 appears to act by increasing agonist-induced phosphatidyl inositol (PI) turnover.…”
Section: Discussionsupporting
confidence: 61%
“…In our present study, we found that the preconfluent cells grown in 0.03 mM Ca had an acute Cai response to 2 mM Cao, and this response is further enhanced when cells were treated for 24 h with 1,25(OH) 2 D 3 . A similar effect of 1,25(OH) 2 D 3 on Cai has been observed in other cell systems (Hruska et al, 1988;Bikle, 1990;Pillai et al, 1995;Mozzetti et al, 1988). In these systems, 1,25(OH) 2 D 3 appears to act by increasing agonist-induced phosphatidyl inositol (PI) turnover.…”
Section: Discussionsupporting
confidence: 61%
“…Highest levels of VDR in mammary gland are seen during lactation, being maximal at 3 days post partum when the concentration of calcium in milk is highest (Colston et al 1988). Addition of 1,25(OH) 2 D 3 to mammary gland explants increased VDR expression and enhanced calcium uptake (Mezzetti et al 1988). Circulating concentrations of 1,25(OH) 2 D 3 are increased during pregnancy and lactation and recent studies have demonstrated the presence of 1α-hydroxylase in normal breast tissue (Friedrich et al 2000).…”
Section: Vdr Expression In Mammary Tissue and Breast Tumoursmentioning
confidence: 97%
“…Furthermore, 1,25(OH) 2 D facilitates the cellular uptake of calcium from circulating blood (25). It has been shown that the addition of 1,25(OH) 2 D to mammary gland explants enhances calcium uptake into its functionally differentiated epithelial cells (27). On the other hand, circulating levels of calcium influence the activity of renal 1-a-hydroxylase and thus the circulating concentration of 1,25(OH) 2 D (26).…”
Section: Sources and Metabolismmentioning
confidence: 99%